Development of socioeconomic disparities across the EU 2004+ countries - Applová, Petra (Univerzita Pardubice, 2016)
The aim of this paper is to determine whether it is possible, in line with the purpose of the cohesion policy, to identify the elimination of disparities across the EU 2004+ countries and their cohesion regions, as measured by a relevant method of geographical analysis of disparities. The disparities were assessed, based on the indicator of gross domestic product per capita, both for each country as a whole and for individual cohesion regions. We have chosen the Theil index as the primary method of assessment, with the results then being checked using the Adjusted Geographic Concentration index (AGC). Both methods have consistently shown that, although there are disparities in the GDP per capita indicator among the countries and their cohesion regions, the disparities can be qualified as relatively low (with the exception of Hungary) based on the values gained using the two methods. Regarding the actual development of disparities, the Theil index identified a significant increase, especially after the crisis year of 2008, while the harmonized AGC index of production revealed, with regard to the different development of individual national indices (stagnation, decline and growth), that the development of discrepancies in wealth creation has not changed.
Keywords: regional disparities; Theil index; concentration of production; Adjusted Geographic Concentration index; O57; R11